PERANCANGAN SISTEM PENGATURAN LAMPU TAMAN KOTA KISARAN MENGGUNAKAN KENDALI KOMPUTER - Purnomo, Nopi; Abadi Tanjung, Akhir; Oktopanda (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2022)
City park lights are lighting or lighting that can display the beauty of city parks at night. Most city governments often find it difficult to control their city park lights so that the lighting in city parks is erratic and irregular. In this case, it is very necessary to build an arrangement or control of city park lights such as traffic light based on digitalism to automatic control using computerization. The research method used is the SDLC (System Development Life Cycle) method. By building a simulation system for controlling city park lights using the Visual Basic programming language, it can be useful for city governments in controlling city park lights efficiently and effectively.